Prevalence and associated factors of common childhood illnesses in sub-Saharan Africa from 2010 to 2020: a cross-sectional study - Adugnaw Zeleke Alem; Kegnie Shitu; Demiss Mulatu Geberu; Bezawit Mulat; Daniel Gashaneh Belay; Dagmawi Chilot (BMJ Open, 2022)
Objective This study aimed to assess the prevalence and determinants of common childhood illnesses in sub-Saharan Africa.Design Cross-sectional study.Setting Sub-Saharan Africa.Participants Under-5 children.Primary outcome Common childhood illnesses.Methods Secondary data analysis was conducted using data from recent Demographic and Health Survey datasets from 33 sub-Saharan African countries. We used the Kids Record dataset file and we included only children under the age of 5 years. A total weighted sample size of 208 415 from the pooled (appended) data was analysed. STATA V.14.2 software was used to clean, recode and analyse the data. A multilevel binary logistic regression model was fitted, and adjusted OR with a 95% CI and p value of ≤0.05 were used to declare significantly associated factors. To check model fitness and model comparison, intracluster correlation coefficient, median OR, proportional change in variance and deviance (−2 log-likelihood ratio) were used.Result In this study, the prevalence of common childhood illnesses among under-5 children was 50.71% (95% CI: 44.18% to 57.24%) with a large variation between countries which ranged from Sierra Leone (23.26%) to Chad (87.24%). In the multilevel analysis, rural residents, mothers who are currently breast feeding, educated mothers, substandard floor material, high community women education and high community poverty were positively associated with common childhood illnesses in the sub-Saharan African countries. On the other hand, children from older age mothers, children from the richest household and children from large family sizes, and having media access, electricity, a refrigerator and improved toilets were negatively associated.Conclusions The prevalence of common illnesses among under-5 children was relatively high in sub-Saharan African countries. Individual-level and community-level factors were associated with the problem. Improving housing conditions, interventions to improve toilets and strengthening the economic status of the family and the communities are recommended to reduce common childhood diseases.